The Phonemic Inventory of Sikles Gurung - Ronkos, Danielle (Nepalese Linguistics, 2022)
This paper describes the consonant and vowel phonemes of the variety of Gurung, or Tamu Kyui, spoken in Sikles Village. Unlike other documented varieties, Sikles Gurung is analyzed with contrastive vowel duration, word-initial obstruent voicing, and two register categories. This analysis is supported by data collected with the help of Sikles speakers living in Nepal and New York City.